2007
DOI: 10.1073/pnas.0701117104
|View full text |Cite
|
Sign up to set email alerts
|

The Nestin progenitor lineage is the compartment of origin for pancreatic intraepithelial neoplasia

Abstract: To determine the cell compartment in which initial oncogenic mutations occur in pancreatic ductal adenocarcinoma (PDAC), we generated a mouse model in which endogenous expression of mutated Kras (Kras G12D ) was initially directed to a population of pancreatic exocrine progenitors characterized by the expression of Nestin. Targeting of oncogenic Kras to such a restricted cell compartment was sufficient for the formation of pancreatic intraepithelial neoplasias (PanINs), putative precursors to PDAC. PanINs appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
108
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(115 citation statements)
references
References 27 publications
6
108
1
Order By: Relevance
“…Recent studies have suggested that centroacinar cells or nestin-positive cells may act as progenitor cells in the pancreas and may be target cells for transformation in pancreatic tumorigenesis. 28,29 Whether either, or both, of these cell types are the cell of origin in our model is a provocative idea that remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that centroacinar cells or nestin-positive cells may act as progenitor cells in the pancreas and may be target cells for transformation in pancreatic tumorigenesis. 28,29 Whether either, or both, of these cell types are the cell of origin in our model is a provocative idea that remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…42 Overall, the location of nestin-GFP cells, their behavior in vitro and in vivo, and the Expression of nestin in these bulge cells with stem-like properties parallels findings from our group and others that this intermediate filament marks stem/progenitor cells in other tissues as well; examples now include neural stem cells, liver oval cells, satellite cells in the muscle, stem cells in the pancreas, and progenitors of Leydig cells. 10,26,39,[43][44][45][46] This raises an intriguing question of whether expression of nestin simply marks the stem/progenitor state of the cells or contributes actively to this state.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we wish to emphasize that the observations in the current study do not negate the possibility that mPanINs might also arise after activation of oncogenic Kras in additional nonacinar cell types. For example, Korc and colleagues have demonstrated that activation of oncogenic Kras in nestin-expressing cells also results in mPanIN formation (36). Nestin is a marker of progenitor cells, and nestin-positive progenitors contribute to the formation of the differentiated acinar cells (37).…”
Section: Discussionmentioning
confidence: 99%